Efisiensi Penggunaan Media Kartu Suku Kata Bergambar untuk Meningkatkan Kemampuanmengeja Kata pada Peserta Didik Kelas IV Tunagrahita Ringan - Lake, Anna; Wangge, Vinsensius; Selan, Ot Bil Wilson; Liunokas, Oded; Ajito, Timoteus (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study is to improve the ability to spell words by using pictorial syllable media for fourth-grade students at SDLB Negeri Kota Radja. This study uses the Classroom Action Research (CAR) method. The subjects of this study consist of four students with mild intellectual disabilities in the fourth grade at SDLB Negeri Kota Radja, comprising one female student (NF) and three male students (AA, KN, RN). Data collection in this study is based on the results of spelling ability tests, observations of student involvement, and documentation as supplementary data. The results of the study using pictorial syllable media can improve the spelling ability of fourth-grade mild intellectual disabilities students in SLB Negeri Kota Radja. This is evidenced by the increase in scores of AA subjects in the pre-test getting a score of 45, post-test cycle I getting a score of 60 and post-test cycle II getting a score of 75. NF subjects in the pre-test getting a score of 45, post-test cycle I getting a score of 65 and post-test cycle II getting a score of 80. KN subjects in the pre-test getting a score of 50, post-test cycle I getting a score of 75 and post-test cycle II getting a score of 80. RN subjects in the pre-test getting a score of 50, post-test cycle I getting a score of 60 and post-test cycle II getting a score of 75. Thus, it can be concluded that picture card syllable media can be used as an alternative in improving the ability to spell words in children with mild mental retardation.